Using linkography to compare creative methods for group ideation. (September 2018) - Hatcher, G.; Ion, W.; Maclachlan, R.; Marlow, M.; Simpson, B.; Wilson, N.; Wodehouse, A.
Abstract : This paper compares a new creative design method, based on the principles of drama improvisation, with brainstorming. The evolution and development of the Design Improv method is reviewed, and the results of an evaluation of both methods in controlled team ideation sessions are documented. The creative characteristics relevant to their quantitative and visual interpretation are analysed using linkography, identifying the most prominent variations in performance with respect to inter-connectedness, parallel thinking and idea diversity. We describe an adapted and expanded process for robust linkograph development and reflect on the value, challenges and limitations of both the linkograph creation and the perceptive insights they can provide. Highlights: Detailed guidance using linkography to understand ideation processes. Benchmarking of a new ideation method with brainstorming using our adapted approach. Methods contrast on inter-connectedness, progressiveness, diversity and productivity. A reflection on the value, challenges and limitations of the study and linkography.